ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA PERIODE 2011 – 2014 - DITA DWI APRILIA (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The purpose of this study was to determine the effect of returns on shares of consumer goods sector companies in the Indonesia Stock Exchange in the period 2011 - 2014. The population in this study were 38 companies listed on the Indonesia Stock Exchange in 2011-2014, and based on purposive sampling method. The results showed that variable return on assets had a significant effect on returns, while the debt to equity ratio and current ratio had no significant effect on stock returns. Simultaneously the variables of debt to equity ratio, return on assets, and current ratio have no significant effect on stock returns on the consumer goods sector companies in the Indonesia Stock Exchange in the period 2011-2014.